Intravenous immunoglobulin in the management of idiopathic inflammatory myositis: A single centre retrospective review - Jeet Hemantkumar Patel; Lalit Duggal; Ved Chaturvedi; Neeraj Jain; Gurbir Bhandari; Mayank Gupta (Indian Journal of Rheumatology)
Objective: Intravenous immunoglobulin (IVIG) has been used in the treatment of severe idiopathic inflammatory myositis (IIM) in the past. We conducted a retrospective analysis of IIM cases and compared patients who received IVIG with those who did not. Methods: Electronic records from the year 2015–2019 were searched for myositis cases using the terms “myositis, inflammatory myositis, autoimmune myositis.” Cases with dermatomyositis, polymyositis, necrotizing autoimmune myositis, and connective tissue disease myositis/overlap myositis were included (n = 28) and those with infectious or granulomatous myositis were excluded (n = 7). Relevant data were noted. Participants were classified into cases and controls based on IVIG use for treatment. Results were expressed as median and interquartile range. Nonparametric testes were used for comparisons. Results: Word search revealed 35 cases of myositis. Of them, 28 patients were included in the study. From these patients, ten patients had treatment with IVIG and 18 had not. The median age was 49.5 (39.5, 57) years, and disease duration 5.5 (2.5, 12) months. IVIG-treated patients had a more extended hospital stay and less arthritis (P < 0.05). A common indication of IVIG use was esophageal ± respiratory muscle weakness (n = 5/10). In the IVIG group, there was a higher rate of pulse glucocorticoids use (P = −0.02); however, the use of other drugs was similar. Sepsis, gastrointestinal complications, and pneumonia were higher in IVIG-treated patients (P < 0.05). IVIG-treated patients had a higher mortality rate and lower response compared to controls (P < 0.05). Conclusion: IVIG is often the drug of choice for patients with infections in IIM in the Indian setting. Although the IVIG group suffered high mortality, confounding factors, and small sample size, limit conclusions on the usefulness of IVIG in IIM. However, this study showed that IVIG might not alleviate infections complicating IIM cases. Further studies are required.